Uninvited Guests. Circassian Migrants in the South Slavic Lands (1860s–mid-1870s) - Popek, Krzysztof (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
In the 19th century, the Ottoman Empire became a destination for Muslims fleeing from the newly created and expanding Balkan states, as well as the Black Sea coast and the Caucasus taken over by the Russians. One of the largest groups were the Circassians, whose resistance against the Romanov state collapsed at the turn of the 1850s and 1860s. It resulted in mass departures: the scale of Circassian emigration to the Ottoman Empire has been estimated at between 200,000 and a million people in the second half of the 19th and the first decade of the 20th century. They made their way to Anatolia, but also to South Slavic lands – in the 1860s, 83,000 refugees were sent to the sanjaks of Adrianople, Vidin, Silistra, Sofia, Ruse, Svishtov, Niš, and Priština. Their fate proved no easier than in the Russian-controlled North Caucasus due to conflicts with the local population. The Circassians gained an extremely negative reputation among Bulgarians and Serbs, which is reflected in historiography and historical memory. The research presented in this article was financed by a grant from the Polish National Science Center: Social Changes of the Muslim Communities in Bosnia-Hercegovina and Bulgaria in the Second Half of the 19th and at the Beginning of the 20th Century: Comparative Studies (2020/39/B/HS3/01717).